Ruptured Suprasellar Dermoid Cyst Treated With Lumbar Drain to Prevent Postoperative Hydrocephalus: Case Report and Focused Review of Literature - Blitz, Sarah E.; Bernstock, Joshua D.; Dmytriw, Adam A.; Ditoro, Daniel Francis; Kappel, Ari D.; Gormley, William B.; Peruzzi, Pierpaolo (Frontiers in Surgery, 2021)
Ruptured intracranial dermoid cysts are extremely rare. Standard treatment consists of endonasal decompression or craniotomy with evacuation and copious irrigation of subarachnoid spaces to remove any disseminated cystic contents. Disseminated fat particles in the subarachnoid space may be the cause of further sequalae, including the subsequent development of chemical meningitis and hydrocephalus. Here, we present a case of ruptured suprasellar dermoid cyst treated with craniotomy for emergent optic nerve decompression, followed by postoperative hydrocephalus successfully treated with lumbar drain. We describe a 30-year-old man with a history of migraines who presented with acute onset of headache, photophobia, nausea, vomiting, and vision loss in the left eye. Head CT and brain MRI demonstrated a ruptured suprasellar dermoid cyst with associated mass effect on the optic nerves and frontal lobes as well as fat attenuation material within the subarachnoid spaces. The patient underwent left frontotemporal craniotomy for cyst resection and developed non-obstructive hydrocephalus on postoperative day 1, refractory to external ventricular drainage. Placement of a lumbar drain cleared the subarachnoid space of debris derived from the ruptured dermoid cyst, and the hydrocephalus resolved. The patient did not require permanent CSF diversion. Intracranial dermoid cysts are uncommon, and rupture is a rare event. Standard surgical treatment with craniotomy for evacuation may leave disseminated dermoid contents and fat particles throughout the subarachnoid spaces. We highlight a case of ruptured suprasellar dermoid cyst with postoperative communicating hydrocephalus treated with lumbar drain when external ventricular drain (EVD) was ineffective. Review of the current literature reveals inconsistent findings on the effects of remaining fat particles. In cases with clinical evidence of increased intracranial pressure due to non-obstructive hydrocephalus attributable to chemical meningitis, temporary lumbar drainage is an option to be considered before committing the patient to permanent shunting.